The association between income inequality and mental health: Social cohesion or social infrastructure? - Richard Layte; Bertrand Maître (The Economic and Social Research Institute (ESRI), 2009)
A large literature has emerged around the strong association between income inequality and average life expectancy and a range of health outcomes including mental well being. Three possible explanations for the association have been offered: that the association is a statistical artefact; the 'social cohesion hypothesis' and lastly, the 'neo-materialist hypothesis'. We examine the ability of these hypotheses to explain the link between income inequality and mental well being in data from 30 countries from the European Quality of Life Survey (2007). Our results offer support to the social cohesion and neo-materialist explanations but evidence for the neo-materialist hypothesis is strongest. Measures of expenditure on social protection and the quality of a range of social services reduce the coefficient measuring income inequality by over two thirds and render it insignificant. However, variables measuring social cohesion such as trust in others, civic participation and social contact reduce the income inequality coefficient by 44% and provide the best fitting model as measured by AIC value.
Keywords: 330; Soziale Ungleichheit; Gesundheit; Zufriedenheit; Psychische Störung; Einkommensverteilung; Sozialer Status; Gesundheitsfinanzierung; EU-Staaten